A rare cause of kyphosis with low backache - “Scheuermann’s disease”: “Osteochondritis deformans juvenilis dorsi” - Bakshi, Vipin Kumar; Chowdhary, Jai; Verma, Anand Prakash; Baberwal, Mool Chand (International Journal of Research in Medical Sciences, 2017)
An uncommon case of Scheuermann’s disease (Apprentice’s spine) is being reported for two simple reasons- firstly, to show that it is a self-limiting disease which needs only proper observation, extension exercises & extension spinal brace and secondly, it becomes a diagnostic riddle when osteolytic lesion is seen in epiphyseal plates of adjacent vertebral bodies in an adolescent. Radiology and Imaging are needed for the early and accurate diagnosis and to differentiate it from other causes of kyphosis. Hence, it stressed the need to publish this condition not only for its rarity but also for its diagnostic puzzle to differentiate it from other conditions. Here we report a case of an adolescent male of 17 years with poor posture/slouching, fatigue, mild pain in lower thoracic area of spine (low backache), stiffness and loss of flexibility with radiological and MRI findings.